Efeitos letais e subletais de extratos vegetais alcoólicos sobre Chrysodeixis includens (Walker, 1858) (Lepidoptera: Noctuidae) - Warmling, Jheniffer Valmira (2018)
Chrysodeixis includens (Walker, 1858) (Lepidoptera: Noctuidae) is considered an important defoliation pest, with a polyphagous habit, as it affects several crops, including beans, cotton and soybeans. In organic production systems there are few alternatives for its control, so that studies of alternative control methods are necessary. In this sense, the objective of this work was to evaluate the lethal and sublethal effect of hydroalcoholic plant extracts and purified fractions on C. includens under laboratory conditions and to identify the secondary metabolites through high performance liquid chromatography. For this, the lethal effect of hydroalcoholic extracts of different plant species, at 10%, on C. includens was evaluated. The extract that caused the highest percentage of mortality was selected and fractionated with different extractive solvents (hexane, dichloromethane and ethyl acetate) and evaluated at concentrations 10; 5; 2.5; 1.25 and 0.625%, on larvae of C. includens. From the results found, the LC50 was determined and the lethal and sublethal effects (duration of the larval period, pupation, pupal weight, sex ratio, emergence, male and female longevity, oviposition and egg viability) were determined. In addition, the secondary metabolites of the purified fractions were identified by means of liquid chromatography. All extracts evaluated showed a lethal effect for C. includens, except for Beccharis genistelloides. The extract of Ricinus communis was the cause of the highest percentage of mortality, 56.66%. Among the purified fractions, the hexane fraction caused the highest lethal effect, as it showed an insecticidal effect at all concentrations, and showed the lowest average lethal concentration of 0.020 (20000ppm). None of the purified extracts and fractions caused sublethal effect on larvae, pupae and adults. In the evaluation of the major compounds, ethyl acetate was identified as: acegenic acid, vanillic acid and rutin, and for crude extract syringogenic acid and rutin were found. It was not possible to detect, from the standards used, chemical compounds in hexane and dichloromethane fractions. Extracts of R. communis have insecticidal potential for the control of C. includens in the laboratory, suggesting that complementary studies in semi field and field are performed.